The Impact of Lockdown during COVID-19 Pandemic on Physical Activity: a Web-based Cross-sectional Survey - Cabral,Filipe (2022)
Abstract Introduction: Home lockdown enforced during COVID-19 pandemic may have affected individuals’ lifestyles and, possibly, their physical activity (PA) levels. In this study, we aimed to assess changes in Portuguese PA levels during lockdown. Methods: We conducted an online survey based on the Special eurobarometer public opinion survey on sports and physical activity in April 2020 in order to collect data about the Portuguese PA levels before and during the home confinement period. PA was assessed by three outcome variables: (i) compliance with World Health Organization (WHO) aerobic PA recommendations, (ii) daily sitting time, (iii) and weekly walking time, with pre- lockdown and during lockdown levels being compared for each. Multinomial regression models were used to identify variables that were associated to changes in PA levels. Results: We obtained 1281 responses (36.4% males). Most participants had high academic levels (73%) and were employed (76.3%). Lockdown was associated with significant decreases in aerobic PA levels (50.0% participants met WHO recommendations for aerobic PA levels before lockdown versus 38.8% during that period; p<0.001) and average weekly walking time (97.2 versus 72.4 minutes; p<0.001), as well as with increases in daily sitting time (p<0.001). We did not identify variables consistently associated with increasing or decreasing PA during lockdown. Conclusion: Home lockdown during COVID-19 pandemic is associated with a decrease in PA levels. In the likely event of another waves, when confinement may again be implemented, these data can be used to better prepare and to promote PA during that period.